Increasing resistance to globalization: The role of trade in tasks - Hartmut Egger; Christian Fischer (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
We show in this paper that trade in tasks can explain increasing resistance to globalization in industrialized countries. In a traditional trade model of a small open economy, we demonstrate that schooling provides protection against losses from trade if trade increases the relative price of the skill-intensive good. Furthermore, increasing public schooling expenditure may help securing support for trade reform by a majority of voters. However, this conclusion is no longer true, if education provides task-specific skills and trade in tasks makes some of these skills obsolete in the open economy. In this case, increasing public schooling expenditure may be of limited help to secure support for trade reform by a majority of voters, even if the reform is welfare-improving. Our analysis suggests to change the education system to one that provides broader, less-specialized skills in order to facilitate trade reforms. Although such skills may be less productive, they do not become obsolete in the open economy and therefore increase the likelihood that a proposal for a welfare-improving trade reform is successful in a referendum.
Keywords: F11; F50; D72; I28; 330; Resistance to globalization; Trade in tasks; Public education; Majority voting